PENGEMBANGAN PARADIGMA BARU KEILMUAN DAN KELEMBAGAAN PENDIDIKAN NON FORMAL - Sodiq A. Kuntoro (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
According to the education law of Republic of Indonesia in 2003, non-formal education is implemented to facilitate the citizen to get education and it functions as substitution, supplement, and complement to formal education. The role of non-formal education is to contribute the implementation of lifelong education as a new approach to education. This new approach is different from the education under present systems that involve the attempt to integrate the different parts of education with the concern for the development of person in intellectual, emotional, social, and vocational aspects. The present non-formal education activities need to expand their activities to create opportunity of education wider and to cover incidental learning as a part of learning activities in society.